Did urban agglomeration development planning policies accelerate urban population decline? A quasi-natural experiment based on urban agglomeration development planning policies in China - Jiang, Aiqing; Shao, Qing; Zhang, Songlin (Frontiers in Sustainable Cities, 2025)
IntroductionTo promote integrated development of large, small, and medium-sized cities, Chinese governments have successively implemented urban agglomeration development planning policies (UADPPs). However, UADPP may intensify the siphoning effect of big cities on smaller peers within urban agglomeration (UA), accelerating population decline in small and medium-sized cities (SMCs) and undermining integration goals. This study investigates the relationship between UADPP and population decline of SMCs in UA, uncovers the logical mechanisms driving this relationship, and conducts heterogeneity analysis to explore the variations from urban types, urban agglomeration types and regions.MethodsUsing prefecture-level city data (2011–2022), this study employs a quasi-natural experiment based on the Chinese State Council-approved UADPPs, using a difference-in-differences (DID) approach to identify the relationship between UADPP and population decline of SMCs in UA. This paper uses the urban population decline rate to reflect the extent of urban population decline. The core explanatory variable of this paper is represented by whether the UADPP where the city is located has been approved by the Chinese State Council. The control variables include Built-up area (lnarea), Economic development (gdpr), Wage (lnwage), Governmental intervention (gov), and younger workers (stud).ResultsResults show that UADPPs strengthen the agglomeration effect of large cities, which triggers the siphoning of resources from surrounding SMCs. Meanwhile, UADPP, facilitating free flow of production factors, drives population migration from SMCs to large ones and accelerates the population decline in SMCs. Robustness tests confirm the validity of this conclusion. Additionally, the heterogeneity analysis reveals that the effect of UADPPs on accelerating urban population decline varies across different city types, urban agglomeration types, and regions. This effect is notably more pronounced and statistically significant in small cities, urban agglomerations characterized by low population agglomeration, and the central regions.DiscussionThese results highlight that the UADPP will accelerate the population decline of SMCs in UA. Policy implications include mitigating the administrative hierarchy-driven siphoning effects, leveraging local resources to cultivate characteristic industries and optimize talent ecosystems in SMCs, actively integrating into global value chains and constructing the agglomeration-economy-driven urban development model.